PENINGKATAN TEKNIK LOMPAT JAUH GAYA JONGKOK MELALUI MODIFIKASI SARANA DAN PRASARANA SDN 223 PALEMBANG - Hidayat, Arif; Samson, Samson (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2017)
The purpose of this research is to know the technique of long jump style squatting through modification of facilities and infrastructure. This research manifests classroom action research. The subjects of this research are the students of grade V of SDN 223 Palembang which is 25 students. Data collection techniques are tests and observations. The technique of data analysis is done descriptively and calculate the average percentage of long jump technique of squatting style. The results showed that the average score of the students on the initial test was 66.25, the first cycle was 71.75, and the second cycle was 82.00. The average increase in the long jump style of squat from the initial test to cycle 1 is 5.5; from cycle 1 to cycle 2 averaging 10.25. The total increase reached 15.75. The results of this study can be concluded that there is an increase in learning results of the long jump technique of squatting style through the modification of facilities and infrastructure in grade V students of SD Number 223 Palembang.